Threats to Investment in Ukraine’s National Economy in Terms of Instability, Preventive Measures - Namliieva Natalia V. (Bìznes Inform, 2019)
The first priority of sustainable development of the national economy is to intensify Ukraine’s investment activities by identifying and neutralizing existing threats, preventing them from occurring in the future and developing directions to minimize them. The article is aimed at identifying existing threats to investment in Ukraine’s national economy in the face of instability and defining preventive measures. In the course of research the author has identified the following threats to investment in Ukraine’s national economy in the face of instability: the armed confrontation in eastern Ukraine; rising inflation; reducing Ukraine’s economic resilience; lack of positive political developments in the external situation; loss of economic ties and strategic partners; directing the State budget to military operations; fastidious demands from foreign financial partners. A prerequisite for activizing the process of investing in the national economy, which provides for its stabilization and development is the development of measures to minimize and prevent threats to investment along with government support for this process. Two main forms of the State support for investment activities are topical: direct (most often financial) and indirect (mediated). In order to activate the State investment regulation, it is proposed to implement a number of measures in the economic, legislative, information spheres, as well as the application of industry and organizational measures, improving the institutional and financial environment and active propaganda measures. A promising direction for further research appears the development of criteria and indicators of assessing the feasibility of investments in various sectors of the national economy both by other countries and by Ukrainian investors.